Spatiotemporal patterns of individual and multiple simultaneous severe weather events co-occurring with power outages in the United States, 2018–2020 - Do, Vivian; Wilner, Lauren B.; Flores, Nina M.; McBrien, Heather; Northrop, Alexander J.; Casey, Joan A. (PLOS climate, 2025)
In the United States, severe weather-driven power outages are increasing in frequency and duration, likely with health consequences. Previous studies examined individual severe weather events (e.g., heatwaves) and focused on large outages in metropolitan areas. Here, we described nationwide spatiotemporal patterns of individual (e.g., tropical cyclone alone) and simultaneous (e.g., tropical cyclone + anomalous heat) severe weather events co-occurring with 8+ hour outages. We used hourly county-level PowerOutage.us data from 2018–2020 to define 8+ hour outages as whenever the daily proportion of customers without power was ≥0.1% for ≥8 continuous hours. We conducted analyses at the daily and county (county-day) level and identified county-days with severe weather events, including anomalous cold, anomalous heat, anomalous precipitation, snowfall, tropical cyclones, and wildfire. Of 1,657 counties with reliable outage data, 1,205 (72.7%) experienced an 8+ hour outage co-occurring with an individual severe weather event, and 904 (54.6%) with multiple simultaneous severe weather events. Anomalous precipitation events co-occurring with outages were the most common, affecting 1,170 (70.6%) counties. These outages concentrated along the Gulf Coast, the Northeast, Michigan, and Southern California. Co-occurrence with anomalous heat happened the second most frequently, affecting 839 (50.6%) counties, mostly in Southeastern states. Among all county-days with a severe weather event, tropical cyclones–though rarer and primarily affecting the Eastern Seaboard–co-occurred with an 8+ hour outage 24% of the time. On the West Coast, wildfires were increasingly likely to co-occur with weather-related outages from 2018–2020. Among multiple simultaneous weather events, 8+ hour outages co-occurred with anomalous precipitation-anomalous heat on 1,155 county-days in 40 states, anomalous precipitation-tropical cyclone on 705 county-days in 24 states, and anomalous cold-snowfall on 259 county-days in 27 states. Our results can help guide efforts to strengthen the electricity grid, prepare communities for multi-hazard events, and allocate resources for adaptation and recovery.